High Dimensionality Reduction and Immune Phenotyping of Natural Killer and Invariant Natural Killer Cells in Latent Tuberculosis-Diabetes Comorbidity. (21st February 2022) - Kathamuthu, Gokul Raj; Kumar, Nathella Pavan; Moideen, Kadar; Menon, Pradeep A.; Babu, Subash
Abstract : Natural killer (NK) and invariant NKT (iNKT) cells are unique innate lymphocytes that coordinate diverse immune responses and display antimycobacterial potential. However, the role of NK and iNKT cells expressing cytokines, cytotoxic, and immune markers in latent tuberculosis (LTB), diabetes mellitus (DM), or preDM (PDM) and nonDM (NDM) comorbidities is not known. Thus, we have studied the unstimulated (UNS), Mycobacterium tuberculosis (Mtb [PPD, WCL]), and mitogen (P/I)-stimulated NK and iNKT cells expressing Type 1 (IFN γ, TNF α, and IL-2), Type 17 (IL-17A, IL-17F, and IL-22) cytokines, cytotoxic (perforin, granzyme B, and granulysin) and immune (GMCSF, PD-1, and CD69) markers in LTB comorbidities by dimensionality reduction and flow cytometry. Our results suggest that LTB DM and PDM individuals express diverse NK and iNKT cell immune clusters compared to LTB NDM individuals. In UNS condition, frequencies of NK and iNKT cells expressing markers are not significantly different. After Mtb antigen stimulation, NK cell expressing [Type 1 (IFN γ, TNF α, and IL-2), GMCSF in PPD and IFN γ in WCL), Type 17 [(IL-17A), PD-1 in PPD), (IL-17A, IL-17F, and IL-22), PD-1 in WCL], and cytotoxic (perforin, granzyme B in PPD, and WCL)] marker frequencies were significantly reduced in LTB DM and/or PDM individuals compared to LTB NDM individuals. Similarly, iNKT cells expressing [Type 1 (IFN γ, IL-2), GMCSF in PPD), TNF α, GMCSF in WCL), Type 17 (IL-17A), PD-1 in PPD, IL-17F in WCL) cytokines were increased and cytotoxic or immune (perforin, granzyme B, granulysin), CD69 in PPD, perforin and CD69 in WCL] marker frequencies were significantly diminished in LTB DM and/or PDM compared to LTB NDM individuals. Finally, NK and iNKT cell frequencies did not exhibit significant differences upon positive control antigen stimulation between the study population. Therefore, altered NK cell and iNKT cells expressing cytokines, cytotoxic, and immune markers are characteristic features in LTB PDM/DM comorbidities.